Psychiatrization of Society: A Conceptual Framework and Call for Transdisciplinary Research - Beeker, Timo; Mills, China; Bhugra, Dinesh; te Meerman, Sanne; Thoma, Samuel; Heinze, Martin; von Peter, Sebastian (Frontiers in Psychiatry, 2021)
Purpose: Worldwide, there have been consistently high or even rising incidences of diagnosed mental disorders and increasing mental healthcare service utilization over the last decades, causing a growing burden for healthcare systems and societies. While more individuals than ever are being diagnosed and treated as mentally ill, psychiatric knowledge and practices affect the lives of a rising number of people, gain importance in society as a whole and shape more and more areas of life. This process can be described as the progressing psychiatrization of society. Methods: This article is a conceptual paper, focusing on theoretical considerations and theory development. As a starting point for further research, we suggest a basic model of psychiatrization, taking into account its main sub-processes as well as its major top-down and bottom-up drivers. Results: Psychiatrization is highly complex, diverse, and global. It involves various protagonists and its effects are potentially harmful to individuals, to societies and to public healthcare. To better understand, prevent or manage its negative aspects, there is a need for transdisciplinary research, that empirically assesses causes, mechanisms, and effects of psychiatrization. Conclusion: Although psychiatrization has highly ambivalent effects, its relevance mainly derives from its risks: While individuals with minor disturbances of well-being might be subjected to overdiagnosis and overtreatment, psychiatrization could also result in undermining mental healthcare provision for the most severely ill by promoting the adaption of services to the needs and desires of the rather mild cases. On a societal level, psychiatrization might boost medical interventions which incite individual coping with social problems, instead of encouraging long-term political solutions.